TMC2 Modifies Permeation Properties of the Mechanoelectrical Transducer Channel in Early Postnatal Mouse Cochlear Outer Hair Cells - Corns, Laura F.; Jeng, Jing-Yi; Richardson, Guy P.; Kros, Corné J.; Marcotti, Walter (Frontiers in Molecular Neuroscience, 2017)
The ability of cochlear hair cells to convert sound into receptor potentials relies on the mechanoelectrical transducer (MET) channels present in their stereociliary bundles. There is strong evidence implying that transmembrane channel-like protein (TMC) 1 contributes to the pore-forming subunit of the mature MET channel, yet its expression is delayed (~>P5 in apical outer hair cells, OHCs) compared to the onset of mechanotransduction (~P1). Instead, the temporal expression of TMC2 coincides with this onset, indicating that it could be part of the immature MET channel. We investigated MET channel properties from OHCs of homo- and heterozygous Tmc2 knockout mice. In the presence of TMC2, the MET channel blocker dihydrostreptomycin (DHS) had a lower affinity for the channel, when the aminoglycoside was applied extracellularly or intracellularly, with the latter effect being more pronounced. In Tmc2 knockout mice OHCs were protected from aminoglycoside ototoxicity during the first postnatal week, most likely due to their small MET current and the lower saturation level for aminoglycoside entry into the individual MET channels. DHS entry through the MET channels of Tmc2 knockout OHCs was lower during the first than in the second postnatal week, suggestive of a developmental change in the channel pore properties independent of TMC2. However, the ability of TMC2 to modify the MET channel properties strongly suggests it contributes to the pore-forming subunit of the neonatal channel. Nevertheless, we found that TMC2, different from TMC1, is not necessary for OHC development. While TMC2 is required for mechanotransduction in mature vestibular hair cells, its expression in the immature cochlea may be an evolutionary remnant.